STRATEGI MODEL PENGENDALIAN PENYEBARAN VIRUS INFLUENZA - Pratiwi, Noviana; kartono, Kartono (MATEMATIKA, 2008)
Influenza or more popular is called flu is a kind of disease caused by virus which infect system of respiratory. Virus of influenza spread by direct contact with a host, so it is needed a quarantine and isolate program to rein it. By quarantine and isolate, formulation of reproduction number are made, by then is to determine a strategy to rein the virus. As a verification of formula obtained, we study the avian influenza at Central Java on September 2005 â€“ April 2008. Â